Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo de la carrera de Administración Pública paralelo “B” de la Facultad Jurídica, Social y Administrativa, 2023-2024 - Cuenca Morocho, Elena Katherine (2024)
The aim of this Curricular Integration Project was to analyse the relationship between the level of the basic cognitive processes of attention and memory and the levels involved in reading comprehension in first cycle students of the parallel "B" Public Administration course. The research was carried out using a quantitative, descriptive, correlational and cross-sectional approach, with a non-experimental design, with a total sample of 20 students. The instruments used to quantify the two variables were the D2 test that evaluates attention, the RIAS test that evaluates memory and the Instrument to Measure Reading Comprehension in University Students (ICLAU), and Pearson's non-parametric correlation coefficient was used for correlation. The results show that 90% of the students have a low level of selective attention, 80% have a low level of memory and 85% have a low level of reading comprehension. According to the correlation between attention and the levels involved in reading comprehension, Kendal's Tau-b value is 0, 36 according to the interpretation of Pearson's correlation places it in a medium positive correlation. As for the relationship between memory and the levels involved in reading comprehension, it has a Kendal's Tau-b value of 0.10 according to the interpretation of Pearson's correlation, which places it in a weak positive correlation. It is generally concluded that there is a relationship between the two variables.